Algerian media student between the Arabic language and the practice of media rolling - Benarioua, Amel (Journal of Human Sciences, 2021)
The university student in the field of media, communication and audiovisual aspiration , in Algeria, to be one of the strong media competencies that addresses the masses, relying  in that on language as an effective means of  persuasion and news in the  first place . the problem of the linguistic practice of Arabic, especially the practice of the media language, among media students in Algerian universities ,one of the problem raised and whose variables can be feared are mile1- there is weakness among students in practicing the media language at the Algerian  university 2- there is a weakness among  professors in teaching specialization in the media language at the Algerian  university 3- there are  solution to control the practice of the media language in the Algerian university though field study in the faculty of media and audiovisual communication, Salah  Boubnider university Constantine 3, field solutions can be found for these form, including encouragement to control and practice the Arabic language and  then   the media at university, and  to improve and maintain scientific activities that serve the serious and accurate practice of media language  such as simulation or limitation, then creativity and  renewal.